Fribaptismen som fredsrörelse: Fribaptisternas värnpliktsvägran, fredsteologi och fängelsepraktik 1888–1904 - Andréasson, Pascal (Svensk teologisk kvartalskrift, 2025)
In the 1800s, mandatory conscription was introduced in Sweden, meaning that every man was obliged to be trained as a soldier. This article studies a Swedish Baptist offshoot named Fribaptisterna (the Free Baptists), who from their start in 1872 opposed military service. The Swedish government sentenced the Free Baptists to prison and penal work, sometimes for more than a year, and they experienced harassment, ridicule, and sometimes violence. But their determination and long-suffering were strong, resulting in the passing of new laws. From 1902, the Royal Majesty would accept exceptions, and in 1925 a law was passed that made it possible for conscientious objectors to be released from their military duty. This article looks at the forming of a collective pacifistic identity among the Free Baptists. It does so by looking at their monthly magazine, Upplysningens Vän (The Friend of Enlightenment), during 1888-1904. A number of testimonies are studied, in which a recurring claim to oppose military service was "for God's word and my conscience". The theological identity of the Free Baptists was formed in open democratically held meetings, where they together studied the Bible and discussed faith and practices with the conviction of Jesus as the Prince of Peace.